2018 IEEE International Conference on Communications (ICC) 2018
DOI: 10.1109/icc.2018.8422345
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Blind Impulse Detector for Bernoulli-Gaussian Noise in Underspread Channel

Abstract: Impulsive noises widely existing in various channels can significantly degrade the performance and reliability of communication systems. The Bernoulli-Gaussian (BG) model is practical to characterize noises in this category. To estimate the BG model parameters from noise measurements, a precise impulse detection is essential. In this paper, we propose a novel blind impulse detector, which is proven to be fast and accurate for BG noise in underspread communication channels. I. INTRODUCTIONImpulsive noises are w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The relation to the parameters of the B–G model is given by truerightpb=left1expfalse(Afalse), truerightΓ=left1false(1expfalse(Afalse)false)normalΛ.The relations () and () ensure that the probabilities of the impulse occurrence of both models are the same and the total noise powers of both models are equal, that is, () equals to (). According to previous studies [2, 25 33, 34], the value of pb is from 10 −4 to 10 −2 and Γ is from 10 −1 to 10 2 for PLC systems. Nevertheless, we apply wider range of pb and Γ to test the robustness of the parameter estimation.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The relation to the parameters of the B–G model is given by truerightpb=left1expfalse(Afalse), truerightΓ=left1false(1expfalse(Afalse)false)normalΛ.The relations () and () ensure that the probabilities of the impulse occurrence of both models are the same and the total noise powers of both models are equal, that is, () equals to (). According to previous studies [2, 25 33, 34], the value of pb is from 10 −4 to 10 −2 and Γ is from 10 −1 to 10 2 for PLC systems. Nevertheless, we apply wider range of pb and Γ to test the robustness of the parameter estimation.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Works on 5G systems or wireless sensor networks have addressed impulsive noise in communication systems . In the works of Cheffena and Shhab et al, for example, it is shown that the performance of those systems can be affected by the impulsive noise characterized by Gaussian mixtures, such as the type of noise considered in the present paper.…”
Section: Introductionmentioning
confidence: 82%
“…Here we invoke the Narrowband Regression method [17] to cancel periodically fluctuating narrowband interferers from the downsampled measurements. Then we invoke the blind BG impulse detector reported in [16] on the cleaned results to distinguish the spikes from the background noise. An instance of noise preprocessing result is depicted in Fig.…”
Section: Test With Field Measurementsmentioning
confidence: 99%
“…1. The simple BG model is supposed to be applied on impulsive noises in underspread channels, where the impulse width is significantly shorter than the sampling interval, so that the multi-path channel fading can be ignored [16]. Under a very high sampling rate such as 80 MSPS, such approximation does not hold any more, and the noise must be first de-convoluted from an unknown observation matrix before fitted with the BG model, which would complicate the task.…”
Section: Test With Field Measurementsmentioning
confidence: 99%